HUBUNGAN PENGETAHUAN, SIKAP DAN TINDAKAN TENTANG PENYAKIT DEMAM BERDARAH DENGUE (DBD) DENGAN RUMAH POSITIF JENTIK WARGA RT. 003 RW.002 KEL. TEBING KEC. TEBING KABUPATEN KARIMUN: The Relationship of Knowledge, Attitude and Action about Dengue Hemorrhagic Fever (DHF) with Larvae Positive House from Residents of RT. 003 RW. 002 In Kelurahan Tebing, Karimun Regency - Samosir, Kholilah; rizkaramdhaniartie, siti; Iskandar, Iwan; Herdiana, Dora (Poltekes Kemenkes Tanjungpinang, 2021)
The Incidence Rate of Dengue Hemorrhagic Fever (DHF) in Karimun Regency was 92.6 per 100,000 population. Tebing sub-district is the sub-district with the highest number of dengue fever cases, as many as 108 cases, 28 cases of which are in the Tebing sub-district. The purpose of this study was to determine the relationship between knowledge, attitudes and actions of residents about dengue disease with larva positive homes in the RT. 003 RW. 002 in Tebing Village, Karimun Regency in 2021. This research was an analytical study with a cross-sectional approach. The number of samples as many as 98 respondents. There was 32 respondents (32.7%) had good knowledge, there were 50 respondents (51%) had a good attitude, and 19 respondents (19.4%) had good actions against dengue disease. Houses with positive dengue mosquito larvae as many as 23 (23.5%). There was no relationship between knowledge and larvae positive house (Pvalue 0.959 > 0.05) and attitude with larva positive house (P value 0.336 > 0.05). However, the action against DHF was associated with positive larvae (Pvalue 0.000 < 0.05). People should do 3M Plus activities more often and keep their houses clean regularly, not store used goods that have the potential to breed mosquitoes, and sprinkle abate powder.